Peran Kelompok Kerja (POKJA) Pemilihan Pengadaan Barang Jasa Di RSUD Depati Bahrin - Tri Putranto Vindi Kusuma (Ilmiah Institut Citra Internasional, 2021)
The Election Working Group plays an important role in the implementation of public services at the Depati Bahrin Regional Hospital. However, in its implementation there are several things that support and hinder the role of the Election Working Group in the process of procuring goods / services at the Depati Bahrin Regional Hospital, Bangka Regency. This research uses a qualitative approach with descriptive methods. Research informants were determined by purposive sampling, namely the Procurement of Goods / Services in Bangka Regency and the Depati Bahrin Regional Hospital, Bangka Regency and the people who have received health services at the Depati Bahrin Regional Hospital, Bangka Regency. For research instruments through interviews and observations and documents. From the research, it was found that there were several things that hindered the role of the Pokja for the Selection of Goods / Services at the Depati Bahrin Regional Hospital, Bangka Regency. However, many things have been achieved to support the role of the Election Working Group, including the use of SPSE in every package of goods / services procurement, the establishment of an SPI (Internal Supervisory Unit), the use of SIMRS (Hospital Management Information System) which includes logistical elements in it, better coordination. between the Election Working Group and the Goods / Services Procurement Actors of the Depati Bahrin Regional Hospital and the goods / services procurement organization in Bangka Regency that is already permanent. Keywords: Role of Election Working Group, Depati Bahrin Regional Hospital, Procurement of Goods / Services, Barriers, Support